The German equivalents of the Macedonian past-future tense in 10 Macedonian prose works (Slavic Studies, 2024)
The interest in analyzing German equivalents of the past-future tense specific to Macedonian, was sparked by the challenges faced while teaching students The variety of equivalents in German raised questions and dilemmas about the semantic aspects of this tense, which can be expressed in multiple ways. an inductive research analysis was conducted using corpus of 10 original works of Macedonian contemporary prose and their translations into German. The Research began with Koneski’s semantic classification, which was enhanced with suggestions for different combinations and conclusions drawn from the examples analyzed. These findings were then applied to the stylistic, temporal and spatial aspects of the corpus.
Keywords: past-future tense; Macedonian; German; contrastive analysis; prose